Minat Siswa Kelas XI IPS SMA Negeri 5 Batanghari Terhadap Pembelajaran Bola Voli - RAIHAN, RAIHAN DIMAS AULIA P; Adillah, Agung Rizqan (Journal Score, 2026)
This study aims to determine the level of interest of class XI IPS students of SMA Negeri 5 Batanghari towards volleyball learning in the classroom. The background of this study is based on the low attention and interest of some students when participating in volleyball theory lessons in class, although their interest is quite high when participating in practical learning in the field. Learning interest plays a crucial role in the success of the learning process, so a clear picture of student interest is needed to form the basis for developing PJOK learning strategies, especially volleyball material. This study used a quantitative descriptive method with 89 students of grade XI social studies as subjects. Data collection was conducted through a questionnaire consisting of 24 items, covering four indicators of interest: feelings of pleasure, interest, attention, and student involvement. Data were analyzed using percentage techniques to determine the categories of student interest levels. The results of the study showed that most students had a high interest in volleyball learning in the classroom. As many as 78% of students were in the "High" category, 21% were in the "Low" category, and 1% were in the "Very High" category, while no students were in the "Very Low" category. These findings indicate that students generally have a good interest in volleyball learning, although there are still a small number who are less interested, which can be influenced by internal and external factors such as personal motivation, learning comfort, and teacher learning methods.